 # Math - Completing the Square - Challenge

In this lecture we looked at “completing the square” algebraically, which helps us to convert our equations from standard form into vertex form.

For your challenge, convert the following equation into vertex, or squared, form;

y = -1/3x^2 + 10/3x - 16/3

1 Like

Did it a bit different than in the lecture, instead of multiplying both sides I factored the 1/3 out.

2 Likes

I began with y = (-x² + 10x - 16) / 3

3y = -x² + 10x - 16
-3y = x² -10x + 16
-3y = (x - 5)² - 25 + 16
-3y = (x - 5)² - 9
y = -(1/3)(x-5)² + 3

1 Like

y = -1/3(x-5)^2 + 3

1 Like

y = -1/3(x - 5) + 3

Vertex at (5,3)

Good job, @Ajai_Raj. However, there is a little detail missing in your quadratic function.

Oh, right-- it should be -1/3(x - 5)^2

This is giving me flashbacks to math class, lol. Thank god there’s no grades in this course.

Don’t worry @Ajai_Raj. You’re doing great!
Making mistakes is how we learnt and the important thing is that you’re putting in the effort to improve.
Everything will come together with time and practice 1 Like

Here goes.

y = -1/3x^2 + 10/3x - 16/3
-3y = x^2-10x+16
-3y = (x-5)^2-25+16
-3y = (x-5)^2-9
y = -1/3(x-5)^2 +3

1 Like

My biggest problem (and nearly all the time) my pluses and minuses are wrong.

sqrt(2) = 4 = 2 x 2
I meant 2^2 = 4 = 2 x 2

sqrt(-2) = -4, but -2 x -2 = 4
I meant -2^2 = -4, but -2 x -2 = 4 (on my calculator)

so sqrt(-2), should be -1 x sqrt(2) as in -1 x 4 = -4
I meant -2^2, is handled as -1 x 2^2 as in -1 x 4 = -4 ( or in my calulator using -2^2 )

Maybe it is the math semantics … but this makes me mismatching + and - signs …

@FedPete,
I’m a little confused, but I’m assuming that you’re talking about squaring numbers rather than taking the square root of numbers, correct?

If you square 2 you get:
`2^2 = 2 x 2 = 4`

If you square -2, you also get 4, since the two negatives give a positive result when multiplied, so:
`-2^2 = -2 x -2 = 4`

Due to this trait of multiplication, there’s no way to square a number and obtain a negative result - It will always be positive.

If you need a negative result then you’d need to do `-(2^2)` rather than `-2^2`. Since you’d be calculating the `2^2` first, and then multiplying by -1 to flip the sign.

Now, if you’re asking about square roots, then you have to be very careful when dealing with the square root of negative numbers because the answer isn’t a real number.

I hope that helps, but if I’ve misunderstood your question, please let me know.

Yes, I did confuse you!

I meant #^2, not sqrt(#) !!

Now I’m becoming confused again (back and forth …) When I enter this in my mobile phone (android) calculator. Exactly in the way you described, entering keystrokes `-2^2=`, it returns -4 (minus four). But `(-2)^2=` returns 4. So semantics is an issue here …

@FedPete, I just tried it on my phone and you’re absolutely right.
It turns out that the android calculator is a bit rubbish!

If you type in “minus” 2 ^ 2, then calculators will read this as; `0 - 2^2 = 0 - 4 = -4`
So the inclusion of that rogue zero at the front is causing a big problem.

Ideally, you need a calculator that has a +/- button, which let’s you flip the sign on your number.
Failing that, you can get around it by just being very careful with your inputs.

In this case, you want to calculate 0 - 2 first and then square the result.
So you can enter your calculation as; 0 - 2 = ^ 2

This will give you:
0 - 2 = -2
-2^2 = 4

If you don’t have an old scientific calculator kicking about in a drawer somewhere, I’d recommend installing one of the many free scientific calculator apps from the Google Play store.
This will make your life a lot easier and will come in handy as you get further into the course.

1 Like My scientific Casio calculator of 35 years ago (Yes I still own this one), does this math correctly.

THX!

1 Like

y=−(1/3) x^2+(10/3)x −(16/3) −Convert to vertex form
−3y=x^2−10x+16
−3y=(x-5)^2−25+16
−3y=(x-5)^2−9
y=−(1/3) (x−5)^2+3

1 Like
1 Like

y = -1/3 (x - 5)² + 3
Vertex at (5 , 3)

1 Like